Reconsidering the Colonialist and Imperialist Themes of Donald Duck Comics by Carl Barks and Don Rosa - Janet Estherina (STKIP Taman Siswa Bima, 2025)
Donald Duck comics has been a popular part of Indonesian children’s media across its 44 year run which ended in 2020. However, the comic has been subjected to criticism for its depiction of race and colonialism, particularly in the popular works of Carl Barks, which often featured adventure stories set in distant, exotic locations and interaction with native people. This paper reexamined the Donald Duck comics by Carl Barks for its themes of colonialism and imperialism. It also looks at the works of Don Rosa, who often write continuation of Barks’s works for similar themes. This study found that while he often featured ethnic stereotypes in his works, Barks’s portrayal of Western colonialism and imperialism was often ambivalent, reflecting a pessimistic attitude towards Western modernity. This study also found that Rosa did not portray racial caricature like Barks did. He also did both works that did not challenge the assumptions of colonialism and imperialism as well as works that challenged such assumptions. This shows that the portrayal of colonialism and imperialism in Donald Duck comics is complicated and differs between authors and even within authors.